Tradução e adaptação transcultural do banco de itens satisfação com a participação social do patient-reported outcomes measurement information system PROMIS® - (Versão 1.0) para a Língua Portuguesa - Silva, Maria Cristina Lima e (2014)
The aim of this study was to develop a Portuguese version for the \"Satisfaction with Social Participation\" item banks of the Patient-Reported Outcomes Measurement Information System (PROMIS®). This system represents the current \"state of the art\" in Health Related Quality of Life researches (HRQoL) as it allows efficient, valid and responsive measures related to diseases or chronic conditions that affects HRQoL. These item banks are grounded in Item Response Theory (IRT) and can be adapted to the unique characteristics of different clinical populations with the possibility of computerized adaptive testing (CAT) which enhances precision and concision to measures, reducing the respondent burden. The Brazilian version was obtained by iterative steps of translation and back translation, bilingual reviewers committee and pre-testing in the target population. The universal approach and harmonization between the different languages guided all the translation process which culminated in a cultural and linguistically appropriate version for applying in the Brazilian context.